Program Sedekah Sampah Sebagai Pembiayaan Pembangunan Mushollah Sekolah Di SMPN 01 Balung - Muhammad Abdullah Ubaidi; Hartono, Hartono (CV. ITTC INDONESIA, 2025)
School facility financing generally still relies on formal methods, while limited funds are the main obstacle to the construction of a prayer room. The Waste Alms Program at SMPN 01 Balung Jember is presented as an innovative and sustainable solution, which combines waste management and charity values. Waste with sales value is collected by school residents, then sold through cooperation with the main waste bank, and the results are used as a source of funds for the construction of a prayer room. This study aims to examine three main aspects: (1) budgeting is carried out in a participatory manner without official fund allocation, relying on voluntary contributions in the form of waste; (2) bookkeeping is carried out manually by the treasurer in an orderly, transparent, and accountable manner, with complete records and valid transaction evidence; and (3) inspections are carried out directly by the principal as a form of supervision and accountability. The research approach used is a qualitative case study, with data collection techniques through observation, structured interviews, and documentation. Data analysis refers to the Miles, Huberman, and Saldana model with stages of data condensation, data presentation, and drawing conclusions and verification. Data validity is obtained through triangulation of sources and techniques, ensuring that research results are reliable and relevant..